Monocyte Transcriptional Profiling Highlights a Shift in Immune Signatures Over the Course of Illness in Schizophrenia - Melbourne, Jennifer K.; Rosen, Cherise; Chase, Kayla A.; Feiner, Benjamin; Sharma, Rajiv P. (Frontiers in Psychiatry, 2021)
With advanced understanding of the intricate interplay between the immune and central nervous systems in neurological and neuropsychiatric illness, there is renewed interest in the potential contribution of immune dysregulation to the development and progression of schizophrenia. To inform this line of inquiry requires a more nuanced understanding of specific immune changes throughout the course of illness. Here, we utilized a genome-wide sequencing approach to transcriptionally profile circulating monocytes in participants with chronic schizophrenia. These myeloid cells, isolated from whole blood samples, are highly plastic with potentially important disease-modifying functions. Differential gene expression and gene set enrichment analyses, focusing on established monocyte phenotypic signatures, including those related to proinflammatory (‘M1-like’) and protective or tissue remodeling (‘M2-like’) functions, were carried out. We demonstrate an overall enrichment of both ‘M1-like’ (interferon-alpha, interferon-gamma, lipopolysaccharide acute) and ‘M2-like’ (endotoxin tolerance, glucocorticoid acute) monocyte signatures in the participants with schizophrenia compared to non-psychiatric controls. There was no enrichment of the ‘M1-like’ chronic stress signature or the ‘M2-like’ interleukin-4 signature. Using the Molecular Signatures Database Hallmark gene sets list, the ‘interferon response’ was most strongly enriched in schizophrenia compared to controls. Additionally, an exploratory subgroup analysis based on illness duration suggests a shift in monocyte phenotype with illness progression. Specifically, the ‘M1-like’ interferon-gamma signature shows decreased enrichment accompanied by increased enrichment of opposing ‘M2-like’ signatures in participants with a medium illness duration shifting to a strong enrichment of interferon response signatures only in participants with a long illness duration. These findings related to circulating immune cell phenotype have potentially important implications for understanding the role of immune dysregulation in schizophrenia and are a critical consideration for future study design and immune-targeting treatment strategies.